Effects of using the WhatsApp application on language learners motivation: a controlled investigation using structural equation modelling. Issue 1 (2nd January 2023) - Alamer, Abdullah; Al Khateeb, Ahmed
Abstract: The study of language learners' motivation has long been considered a key, determining factor of success in second/foreign language acquisition. Based on self-determination theory (SDT), the more autonomously motivated learners are, the better they engage in an activity. To sustain autonomous motivation, the learners' basic psychological needs (BPN) of autonomy, competence, and relatedness should be satisfied. Nevertheless, the role of these three components and their relation to autonomous motivation in the mobile-assisted language learning (MALL) context has not yet been addressed in the literature. Therefore, a social networking mobile application ( WhatsApp ) has been used to explore how teachers' informal use of such an application relates to an increase in students' motivation. A quasi-experimental design was adopted for two groups of Saudi university students enrolled in the English language department at two major universities (N = 447). The structural model revealed a significant improvement in the effects of Time 1 autonomy on Time 2 autonomous motivation as well as in the effects of Time 1 autonomous motivation on Time 2 autonomous motivation exclusively in the experimental group. The two-time repeated measure of ANOVA substantiated the increase in autonomous motivation exclusively among students in the experimental group. This study contributed to greater recognition of the advantages and challenges of applying WhatsApp as a tool of MALL in the educational system.